THE CORRESPONDENCE OF PROVERBS RELATED TO MONETARY UNITS IN THE ENGLISH AND UZBEK LANGUAGES (International journal of artificial intelligence, 2025)
The article is devoted to the correspondence of money-related proverbs in English and Uzbek languages. It is obviously known that mainly there are three types of correspondence such as fully, partial, and no correspondence of proverbs about money in two languages. Understanding the level of correspondence between these proverbs provides insight into shared human wisdom at the same time the unique cultural perspectives of each society. The analysis of these proverbs allowed the author to identify a number of proverbs about monetary units with their examples.